Formulation and Characterization on Self Nanoemulsifying Drug Delivery System of Eleutherine Palmifolia Extract Employing Short, Medium, and Long Chain Triglyceride - Rahmi Annisa; Yen Yen Ari Indrawijaya; Dewi Sinta Megawati; Ana Fikrotus Zakia (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
Eleutherine palmifolia (E. palmifolia) is a common plant used as an anticancer drug in Kalimantan, Indonesia. The active compound present in it is naphthoquinone, which has low water solubility and needs to be formulated into SNEDDS preparations to improve its dissolution and bioavailability in the body. The dispersion method is used in the preparation of Self-Nanoemulsifying Drug Delivery Systems (SNEDDS) and PEG 400 cosurfactants. Furthermore, this study aims to ascertain the effects of oil on the SNEDDS preparations. The results showed that the effect of the preparations on olive oil, VCO, and oleic acid in the organoleptic test produced dark red, clear, and non functional emulsion. The average particle sizes obtained in the AGF media were 61,10, 774,33, and 211,70 nm; in AIF media it amounted to 211,70, 123,65, and 830,22 nm. The pH value for each formula was 6,8, while the average emulsification time for the AGF media was 24,10, 22,53, and 25,75 seconds, and, lastly, for the AIF media, they were 20,96, 19,62, and 23,74 second.